Animal Models of Maternal Immune Activation in Depression Research - Ronovsky, Marianne; Berger, Stefanie; Molz, Barbara; Berger, Angelika; D. Pollak, Daniela (Current Neuropharmacology, 2016)
Background: Depression and schizophrenia are debilitating mental illnesses with significant socio-economic impact. The high degree of comorbidity between the two disorders, and shared symptoms and risk factors, suggest partly common pathogenic mechanisms. Supported by human and animal studies, maternal immune activation (MIA) has been intimately associated with the development of schizophrenia. However, the link between MIA and depression has remained less clear, in part due to the lack of appropriate animal models. Objective: Here we aim to summarize findings obtained from studies using MIA animal models and discuss their relevance for preclinical depression research. Methods: Results on molecular, cellular and behavioral phenotypes in MIA animal models were collected by literature search (PubMed) and evaluated for their significance for depression. Results: Several reports on offspring depression-related behavioral alterations indicate an involvement of MIA in the development of depression later in life. Depression-related behavioral phenotypes were frequently paralleled by neurogenic and neurotrophic deficits and modulated by several genetic and environmental factors. Conclusion: Literature evidence analyzed in this review supports a relevance of MIA as animal model for a specific early life adversity, which may prime an individual for the development of distinct psychopathologies later life. MIA animal models may present a unique tool for the identification of additional exogenous and endogenous factors, which are required for the manifestation of a specific neuropsychiatric disorder, such as depression, later in life. Hereby, novel insights into the molecular mechanisms involved in the pathophysiology of depression may be obtained, supporting the identification of alternative therapeutic strategies.
Keywords: maternal immune activation